Attention bias for social threat in youth with tic disorders: Links with tic severity and social anxiety. Issue 3 (3rd April 2019) - Pile, Victoria; Robinson, Sally; Topor, Marta; Hedderly, Tammy; Lau, Jennifer Y. F.
ABSTRACT: Many individuals with Tourette syndrome and chronic tic disorders (TS/CTDs) report poor social functioning and comorbid social anxiety. Yet limited research has investigated the role of cognitive factors that highlight social threats in youth with TS/CTD, and whether these biases underlie tic severity and co-occurring social anxiety. This study examined whether selective attention to social threat is enhanced young people with TS/CTDs compared to healthy controls, and whether attention biases are associated with tic severity and social anxiety. Twenty seven young people with TS/CTDs and 25 matched control participants completed an experimental measure of attention bias toward/away from threat stimuli. A clinician-rated interview measuring tic severity/impairment (YGTSS Total Score) and questionnaire measures of social anxiety were completed by participants and their parents. Young people with TS/CTD showed an attention bias to social threat words (relative to benign words) compared to controls but no such bias for social threat faces. Attention bias for social threat words was associated with increasing YGTSS Total Score and parent-reported social anxiety in the TS/CTDs group. Mediation analysis revealed a significant indirect path between YGTSS Total Score and social anxiety, via attention to social threat. Tentatively, these associations appeared to be driven by impairment rather than tic severity scores. Preliminary data suggests that youth with TS/CTD have enhanced attention to threat, compared to controls, and this is associated with impairment and social anxiety. Attention to threat could offer a cognitive mechanism connecting impairment and social anxiety, and so be a valuable trans-diagnostic treatment target.